Small And Medium-Sized Enterprises and The Application of Knowledge Management in Disaster Condition - Pricylia Chintya Dewi Buntuang; Harnida Wahyuni Adda (Universitas Bunda Mulia, 2022)
This study describes the knowledge management applied by small and medium-sized enterprises (SMEs) in both natural and non-natural disaster conditions. SMEs need innovation and creativity to maintain business continuity so the application of knowledge management is important as limited resources greatly affect it. Therefore SMEs need to innovate and show their creativity to get out of the slump caused by the disaster. This study used a quantitative approach by conducting statistical tests and comparative tests. This study involved 200 SMEs affected by natural and non-natural disasters as the population, while the sample size was based on the Slovin formula and was determined randomly. The results of the study showed that there were differences in the knowledge management applied by SMEs during natural and non-natural disaster conditions.